Aqueous extract of Solanum americanum Mill. relieves functional constipation by modulating the enteric nervous system and gut micro-ecosystems - Gao, Xiaoyu; Li, Yanan; Hu, Yifan; Yang, Weixing; Peng, Lei; Sheng, Jun; Tian, Yang; Yao, Lu; Zhao, Yan (Frontiers in Nutrition, 2025)
Solanum americanum Mill. (SA) is a food and medicine homology resource of the Li nationality. In Yunnan folk, people often eat SA “for gut.” However, no studies have been reported on its treatment in constipation. The present study evaluated the laxative activity of Solanum americanum Mill. aqueous extract (SAAE) using loperamide-induced functional constipation (FC) mouse model. The results demonstrated that SAAE is abundant in nucleotides and polysaccharides. The gavage of 300, 600, and 900 mg/kg·bw of SAAE was efficacious in enhancing defecation behavior and the gastrointestinal transit rate of FC mice. Among these doses, 600 mg/kg·bw of SAAE exhibited the best laxative effect. Furthermore, SAAE exerted a significant effect on the colon transcriptome profiles of FC mice, most notably on the neuroactive ligand-receptor interaction and the TNF receptor type 1 (TNFR1) signaling pathway. Among neuroactive ligand-receptor interaction pathway, SAAE significantly affected the levels of 5-hydroxytryptamine, neuropeptide Y, and epinephrine in the serum and colon of FC mice. In addition, SAAE significantly up-regulated the expression of Bcl-XL, an anti-apoptotic protein in the colon. Intriguingly, SAAE also significantly increased the expression of the neuronal markers HuC/D in the colon. This finding suggests that SAAE may alleviate FC by modulating the enteric nervous system. Notably, SAAE alleviated loperamide-induced gut inflammation, damaged gut barrier, and gut microbiota disruption. A significant increase in the relative abundance of Actinobacteriota, Christensenellaceae, Eggerthellaceae, Enterorhabdus, and Eubacterium_brachy_group were observed in the gut of FC mice treated with SAAE. These microbial taxa are closely associated with phenotypic indicators of FC, and it is hypothesized that they may be key taxa in SAAE regulation of the gut micro-ecosystems and enteric nervous system to alleviate FC. These findings may contribute to the enhancement of the value and the efficient utilization of SA resources, laying a theoretical foundation for the development of laxative-related products.